Tinjauan Siyasah Dusturiyyah terhadap Konsep Pengawasan KPK pasca Revisi Undang-Undang Nomor 19 Tahun 2019 - Yusuf, Adzinul Fuadhi; Umardani, Achmad (Manabia: Journal of Constitutional Law, 2025)
This study analyses the impact of the Supervisory Board on the effectiveness of the Corruption Eradication Commission (KPK) following the enactment of Law No. 19 of 2019. This institutional change has sparked controversy as it is considered to limit the KPK's scope of action in eradicating corruption, as reflected in the decline in the Corruption Perception Index (CPI) over the past five years. The study uses a normative juridical approach with primary legal sources in the form of Law No. 19 of 2019 and official KPK documents, as well as secondary sources from legal literature and constitutional studies. The analysis was conducted descriptively, analytically, and deductively to assess the implications of the regulation on the effectiveness of the KPK and its compatibility with the principles of siyasah dusturiyyah, including justice ('adalah), deliberation, and transparency (shafafiyyah). The results of the study show that the existence of the Supervisory Board has the potential to weaken the performance of the KPK, there are pros and cons regarding its formation and authority, and several aspects of the regulation contradict the principles of siyasah dusturiyyah. These findings emphasize the need for regulatory evaluation to ensure that the KPK remains effective while being based on the principles of law and governance that are fair, transparent, and accountable. This research is expected to contribute academically and provide input for the development of KPK institutional reform policies.